2019
DOI: 10.1007/s12630-019-01341-8
|View full text |Cite
|
Sign up to set email alerts
|

A basic anesthesia training program for nurses in Chad: first steps for a south–south academic cooperation program

Abstract: Purpose Safe perioperative care remains a large public healthcare problem in low-and middle-income countries. Anesthesia care provided by trained professionals is one of the essential determinants to address this situation. This article reports the design and implementation of a focused anesthesia educational program for nurses in Chad. Method This program consisted of four full-time courses of one month each, taught in a local hospital. The program included supervised practice in the operating room and post-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The study findings revealed that two third of the studied nurses in youth age, more than one quarter of them had 5 years' experience, and half of them not take training courses. This result was in in an agreement with Kattan (2019) (30) who study results showed that, the majority studied nurses, aged twenty-eight-forty years, and had no previous experience in anesthesia, and most of them not take informal training. It was noticed from the present result that about two thirds of the studied nurses didn't know or had incorrect answer about definition, types and methods of administration of neuromuscular drug before the educational module compared with the majority of them had correct and complete answered after the educational module.…”
Section: Discussionsupporting
confidence: 91%
“…The study findings revealed that two third of the studied nurses in youth age, more than one quarter of them had 5 years' experience, and half of them not take training courses. This result was in in an agreement with Kattan (2019) (30) who study results showed that, the majority studied nurses, aged twenty-eight-forty years, and had no previous experience in anesthesia, and most of them not take informal training. It was noticed from the present result that about two thirds of the studied nurses didn't know or had incorrect answer about definition, types and methods of administration of neuromuscular drug before the educational module compared with the majority of them had correct and complete answered after the educational module.…”
Section: Discussionsupporting
confidence: 91%
“…This aspect is particularly important for low-and middle-income countries ICU's, where high costs and lack of availability of commercial simulators have been described as potential barriers for simulation training implementation. 48,49 A recent survey in France suggests that critical care physicians perform between 2 and 4 PDT per month. 50 In this sense, in infrequent procedures, like BG-PDT, simulation training has even a more important role, 32 because the limited clinical cases residents are exposed to are not invested in learning basic procedural aspects, but rather in capitalizing the specific details before autonomous execution, and in preventing skills decay through continuous training.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a low-cost and easy to construct simulator in the program design allows it to be easily replicated. This aspect is particularly important for low- and middle-income countries ICU's, where high costs and lack of availability of commercial simulators have been described as potential barriers for simulation training implementation 48,49 …”
Section: Discussionmentioning
confidence: 99%